LABOR SECURITY OF UKRAINE: CHALLENGES AND THREATS OF PROVIDING THE NATIONAL ECONOMY WITH PERSONNEL IN CONDITIONS OF SOCIAL INSTABILITY (Regional aspects of productive forces development of Ukraine, 2022)
Introduction. In recent decades, problems of population reproduction have worsened in Ukraine and, as a result, labor safety has worsened. The number of economically active population is constantly decreasing, the labor potential of society is decreasing, and human capital is decreasing as the basis for the formation of personnel of organizations and enterprises. The Covid-19 pandemic has significantly worsened the situation in the labor market.Large-scale external labor migration is a consequence of the lack of decent work in Ukraine, but it threatens the state's labor security and causes an outpouring of intellectual potential.Goal. To highlight in more detail, the problems of labor safety in Ukraine in conditions of social destabilization and especially in the post-covid period, which will cause certain challenges and threats in the formation and use of personnel of territorial communities. The results. The analysis of the demographic situation in Ukraine, its trends, and the study of the structure of the country's labor potential at the macro level made it possible to draw certain conclusions regarding the challenges and threats to labor safety. First of all, intense internal territorial displacement of the population aggravated the problem of employment of migrants, ensuring the production activity of the enterprises that underwent displacement. Labor protection will significantly affect the revival of the labor market, which involves the involvement of workers who have lost their jobs due to the pandemic. In the future, the labor situation in the country will be decisive for the staffing of organizations and enterprises that will resume their full-fledged activities after the end of the pandemic. Local self-government bodies and employment centers will play a special role in the field of accounting, selection, and use of labor resources, and unemployment prevention.